Castration pain and pain alleviation in semi-domesticated reindeer (Rangifer tarandus tarandus) - Nurmi, Hanna (Helsingin yliopisto, 2024)
Approximately 2500−4000 reindeer (Rangifer tarandus tarandus) bulls are castrated annually in Finland, mostly without pain alleviation, in round-ups or winter enclosures. Pain is an important welfare issue and research on other ruminants shows that clamp castration is painful. Reindeer, as prey animals, show modest castration pain. Recognizing pain, understanding the importance of pain alleviation and having appropriate methods and motivation for providing analgesia are all critically important. According to new animal welfare legislation (693/2023), pain alleviation in painful procedures is mandatory in Finland from January 2024 onward. There has been a gap in knowledge on reindeer castration pain behaviours and on the practical means of medicating reindeer, particularly that targeting castration pain alleviation. These semidomesticated, free-ranging animals are not very used to human presence, they are easily excitable, field anesthesia is problematic and capture and prolonged restraint may cause problems, even mortality. Reindeer are prone to stress induced hyperthermia, gastric ulcers and capture myopathy. Pain alleviation in reindeer is challenging. Their wintertime metabolism can slow down by more than 50%, which may have a substantial impact on the pharmacokinetics of different drugs. Sedation and/or narcosis can cause serious side-effects in wild ruminants, especially during harsh winter conditions and hectic roundup situations. Many of the sedative drugs available, especially sedative antagonists, are not accepted for production animal use. Local anesthesia (LA) adds to handling time or handling occasions. The evidence-base is missing on the use of non-steroidal anti-inflammatory drugs (NSAID) in reindeer. These drugs are now used off-label according to the cascade rules of directive EU (2019/6), extrapolating the doses from those for other ruminants. The work embodied in this thesis aims to define pain behaviours and investigate best present pain alleviation practices in reindeer castration. More ...